A narrative analysis of anti-abortion testimony and legislative debate related to Georgia's fetal "heartbeat" abortion ban. Issue 1 (1st January 2020) - Evans, Dabney P.; Narasimhan, Subasri
Abstract: Fetal "heartbeat" bills have become the anti-abortion legislative measure of choice in the US war on sexual and reproductive health and rights (SRHR). In 2019, Georgia House Bill 481 (HB 481) passed by a narrow margin banning abortions upon detection of embryonic cardiac activity, as early as six weeks gestation. The purpose of this study was to distinguish and characterise the arguments and tactics used by legislators and community members in support of Georgia's early abortion ban. Our data included testimony and debate from House Health and Human Services and the Senate Science and Technology Committees; data were transcribed verbatim and coded in MAXQDA 18 using a constant comparison method. Major themes included: the use of the "heartbeat" as an indicator of life and therefore personhood; an attempt to create a new class of persons – fetuses in utero – entitled to legal protection; and arguments to expand state protections for fetuses as a matter of state sovereignty and rights. Arguments were furthered through appropriation by misrepresenting medical science and co-opting the legal successes of progressive movements. Our analysis provides an initial understanding of evolving early abortion ban strategy and its tactics for challenging established legal standards and precedent. As the battle over SRHR wages on, opponents of abortion bans should attempt to understand, deconstruct, and analyse anti-abortion messaging to effectively combat it. These data may inform their tactical strategies to advance sexual and reproductive health, rights, and justice both in the US context and beyond.